2015
DOI: 10.5535/arm.2015.39.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Leisure Activity and Exercise of Chronic Stroke Survivors Using Community-Based Rehabilitation Services in Seongnam City

Abstract: ObjectiveTo clarify how participation in leisure activities and exercise by chronic stroke survivors differs before and after a stroke.MethodsSixty chronic stroke survivors receiving community-based rehabilitation services from a health center in Seongnam City were recruited. They completed a questionnaire survey regarding their demographic characteristics and accompanying diseases, and on the status of their leisure activities and exercise. In addition, their level of function (Korean version of Modified Bart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…reported that the physical activity was more even after stroke. [ 32 ] This difference may be related to the role of perceived risk as a strong motivator to healthy life in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the physical activity was more even after stroke. [ 32 ] This difference may be related to the role of perceived risk as a strong motivator to healthy life in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge only in the study of Yi et al doing art/cultural activities in leisure time was reported by the patients who survived a stroke. 45 Performing creative activities in the Adolescence Leisure Interest Profile 46 and doing craft works in Assessing Adult Leisure Activities 33 however; were reported as art/cultural activities of the non-patient subgroups of the populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, after their discharge, they often do not receive continuous rehabilitation treatment in their community. The number of stroke survivors using community-based public health rehabilitation services is also low 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 99%